2021
DOI: 10.1007/s10562-021-03575-y
|View full text |Cite
|
Sign up to set email alerts
|

Converting Cyclohexanone to Liquid Fuel-Grade Products: A Characterization and Comparison Study of Hydrotreating Molybdenum Catalysts

Abstract: Developing biomass-based strategies for liquid bio-fuels production is promising for the reduction of the aftereffects of fossil fuels. The conversion of lignin-derived intermediates such as cyclohexanone is currently of a great deal of interest. The current study aims to evaluate the molybdenum-based hydrotreating catalysts for the conversion of cyclohexanone in the presence of hydrogen. Catalytic experiments at 400 °C, 15 bar, and a range of WHSV were developed. The experiments reveal that catalyst type and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 102 publications
(144 reference statements)
0
3
0
Order By: Relevance
“…For a better understanding, the pyrolysis process for hydrogen production is presented in the form of a diagram by the authors of (Bakhtyari et al, 2021).…”
Section: Cxhyoz (Biomass) + Heat → Co + H2 + Ch4 + Othersmentioning
confidence: 99%
“…For a better understanding, the pyrolysis process for hydrogen production is presented in the form of a diagram by the authors of (Bakhtyari et al, 2021).…”
Section: Cxhyoz (Biomass) + Heat → Co + H2 + Ch4 + Othersmentioning
confidence: 99%
“…Dicyclohexyl methane was obtained from the above-mentioned feedstocks using Pd/C-HZSM-5, Ru@SILP (Ph 3 -p-NTf 2 ), Pd loaded (C, Al 2 O 3 , BETA, ZSM-5, MCM-41), Pt (111), Ru/Al 2 O 3 -zeolite (HY), SAA-57/Ru-CSA, and MMT-KSF/K-10 catalysts. Hydrodeoxygenation of 2-benzyl-4-ethyl phenol and alkylation of phenol with dibenzyl ether have been reported using an HZSM-5 + Pd/C catalyst system for DCM conversion . Mesoporous silica COK-12, Al 2 O 3 -ZrO 2 /SiO 2 , CoMoOx/Al 2 O 3 and CoMoSx/Al 2 O 3 , Fe-Co/Ni 2 P, alumina supported CoMo and NiMo catalysts, Ru nanoparticles on SiO 2 , Pt/C, Ru/HZSM-5 and Hβ/Pd-C catalysts have also been reported to convert the above starting materials to bi-cyclohexane. Cecilia and co-workers reported on the role of phosphorous in the removal of oxygen from dibenzofuran using Ni 2 P catalysts . Nagai et al reported Mo-supported Al 2 O 3 catalysts employed for carbazole hydrodenitrogenation .…”
Section: Introductionmentioning
confidence: 99%
“…The possible outcome of di-cyclohexyl methane (DCM), bi-cyclohexane (BCH), and decalin (DC) can be synthesized from different feedstocks such as 2-benzyl phenol, diphenyl ketone, , di-phenyl methane, 2-benzyl 4-ethyl phenol or 3-benzyl 4-ethyl phenol, benzofuran, benzyl phenyl ether, phenol with dibenzyl ether, and phenol with benzyl acetate for DCM; dibenzofuran, , dibenzothiophene, carbazole, cyclohexanone, biphenyl, 5,5′-biphenol, and phenol for BCH; and α-tetralone, tetralin, , naphthalene, α-naphthol, , and cyclopentanone for DC. The aforementioned feedstocks have been converted to jet-fuel range hydrocarbons through vapor phase and liquid phase catalytic reactions with various types of metal-containing catalysts.…”
Section: Introductionmentioning
confidence: 99%